What do others think? The why, when and how of using surveys in CBT. (23rd September 2022) - Murray, Hannah; Kerr, Alice; Warnock-Parkes, Emma; Wild, Jennifer; Grey, Nick; Clark, David M.; Ehlers, Anke
Abstract: Surveys are a powerful technique in cognitive behavioural therapy (CBT). A form of behavioural experiment, surveys can be used to test beliefs, normalise symptoms and experiences, and generate compassionate perspectives. In this article, we discuss why and when to use surveys in CBT interventions for a range of psychological disorders. We also present a step-by-step guide to collaboratively designing surveys with patients, selecting the appropriate recipients, sending out surveys, discussing responses and using key learning as a part of therapy. In doing so, we hope to demonstrate that surveys are a flexible, impactful, time-efficient, individualised technique which can be readily and effectively integrated into CBT interventions. Key learning aims: After reading this article, it is hoped that readers will be able to: (1) Conceptualise why surveys can be useful in cognitive behavioural therapy. (2) Implement collaborative and individualised survey design, delivery and feedback as part of a CBT intervention.